1978
DOI: 10.2134/jeq1978.00472425000700040022x
|View full text |Cite
|
Sign up to set email alerts
|

Simazine Residue Levels in Irrigation Water after Ditchbank Application for Weed Control

Abstract: A field study was conducted to determine the amount of simazine [2‐chloro‐4,6‐bis(ethylamino)‐s‐triazine] likely to be found in irrigation water after ditchbank treatment for weed control. Resulting data are useful in evaluating the potential impact of simazine on crops irrigated from sprayed canals. Canals were selected in California, Colorado, and Washington for the application of simazine to both watered and dewatered sites at rates of 2.25 to 7.43 kg/ha. Simazine levels in flowing canal water immediately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the related simazine water residue study (Anderson et al, 1978), the amount of herbicide found in flowing canal water immediately following application to one bank did not exceed 60 Mg/L. Residue levels detected in first flow water samples collected 4 to 6 months after application, peaked at 250 Mg/L within the treated section but decreased rapidly to less than 5 Mg/L.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the related simazine water residue study (Anderson et al, 1978), the amount of herbicide found in flowing canal water immediately following application to one bank did not exceed 60 Mg/L. Residue levels detected in first flow water samples collected 4 to 6 months after application, peaked at 250 Mg/L within the treated section but decreased rapidly to less than 5 Mg/L.…”
Section: Resultsmentioning
confidence: 90%
“…The treatment levels were selected to simulate the maximum level and ten times the maximum that might be expected to enter irrigation water after bank application for weed control. The study was correlated with another activity in which simazine was applied at rates of 2.25 and 4.5 kg/ha to sections of bank along one side of both flowing and dry canals in California, Colorado, and Washington (Anderson et al, 1978). Water samples were taken immediately after herbicide application adjacent to flowing canals and at the time of first spring flow in 1977 from dry application sites.…”
mentioning
confidence: 99%